Risk Analysis of Customers Churn Rate at the Bandung Mandiri Shariâ€™a Bank - Wiryono, Sudarso Kaderi (Jurnal Manajemen Teknologi, 2007)
Shari'a banking are expanding and growing rapidly nowadays, as shown by the increasing market shares at several already existing shari'a banks as well as births of new shari'a banks induced by conventional banks. Such growth is also proven at Bank Shari'a Mandiri (BSM), namely the Bandung Mandiri Shari'a Bank, by a significant increase in the number of its financing customers. Indeed, the increase could not be separated from the churn rate, namely customer migration and absorption from conventional banks or the other existing shari'a banks to Bandung BSM. Financing customer migration thus becomes an important matter to be studied, in order to find out about the driving factors for financing customers' preferences to be made an input for Bandung BSM for planning a strategy to cope with the market share increase. This research was aimed at identifying financing customers' preferences toward Bandung BSM by studying the dominant factors influencing the financing customers to choose and migrate to Bandung BSM and using the factor analysis method to observe the churn rate risks. Samples are taken from a number of Bandung BSM customers, selected through questionnaires. There are three factors influencing customer preferences for choosing Bandung BSM, namely: availability of supporting facilities, leadership, and shari'a. Based on impact-probability matrix analyses, it is shown that there are three attributes that have high probability values, that is, profit sharing system, administrative easiness, and leadership factors. Results of this research also showed that the Bandung BSM churn rate risks were of medium to high probability, and this will greatly impact the bank's performance. Therefore, some real effort is necessary to minimize the churn rate risks.Â Keywords:customer preference, chun rate risk, factor analysis, risk analysis, risk identification, risk measurement, impact-probability matrix